Stability analysis of higher-order delta-sigma allodulators using the describing function method - Lota, Jaswinder; Al-Janabi, Mohammed; Kale, Izzet (IEEE, 2006)
The aim of this paper is to determine the stability of higher-order Delta-Sigma modulators using the Describing Function Method. The maximum stable input limits for third-, fourth- and fifth-order Chebyshev Type II based Delta-Sigma modulators are established. These results are useful for optimising the design of higher-order Delta-Sigma modulators.
IEEE International Symposium on Circuits and Systems -- MAY 21-24, 2006 -- Kos, GREECE